Nitrogen Balance in Female Japanese National Handball Players During Training Camp - Suzuki, Haruka; Ueno, Yuki; Takanouchi, Toshiya; Kato, Hiroyuki (Frontiers in Nutrition, 2020)
Protein requirements for athletes are affected by various factors, including distribution and quality (i.e., amino acid composition) of protein ingestion throughout the day. However, little is known about the protein requirements of elite female athletes engaging in team sports. This study aimed to determine the nitrogen balance and distribution of protein and amino acid intake in elite female handball athletes during training camp. In observational study design, eleven female Japanese national handball players (age 26.9±4.9 years) participated in a 5-day experiment. Nitrogen balance was calculated from the daily protein intake assessed by dietary records and urinary nitrogen excretion. Amino acid intake amounts were organized based on six eating occasions. The average and population-safe protein intake for zero nitrogen balance were estimated as 1.57 and 1.93 g/kg/d, respectively. The protein intake at breakfast, lunch, and dinner and the leucine intake in the three main meals and the morning snack were higher than is recommended by current guidelines for maximizing muscle protein synthesis. The population-safe protein intake in elite female handball athletes was within the range of the current recommendations for athletes (1.2-2.0 g/kg/d). Our results show that it may be possible to improve the distribution and quality of protein ingestion after exercise and before sleep.